Requiem for the Burden of Proof - Nieva Fenoll, Jordi (Revista Ítalo-española de Derecho procesal, 2022)
The burden of proof, a notion specific to the medieval Roman-canonical process but alien to the four Roman procedural systems, ought to have become obsolete with the introduction of the free assessment of evidence. However, doctrinal and jurisprudential inertia in the use of traditional concepts, as well as the conservation of biphasic processes in legal systems of Anglo-Saxon origin, including the Roman-canonical process, have favoured the persistence of a notion that, when observed objectively, has ceased to have any legitimate practical value in current judicial processes.